Analisis Pengaruh Investasi Asing dan Pinjaman Luar Negeri Pemerintah Terhadap Pertumbuhan Ekonomi Indonesia Periode 1981-2014 - Napitupulu, Alexander (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study was to determine: (1) whether or not the relationship between government foreign loans and foreign investment and crisis moneter to economic growth in Indonesia, and (2) a variable used in the form of data of foreign government debt, foreign investment and crisis in Indonesia as well as the level Indonesia's economic growth in the form of data years from 1981 to 2014. This study uses multiple regression analysis. From the results of this research note that (1) foreign loans and foreign investment positive significant effect on economic growth it is shown from the results of research that R Square of 0,951158 Â this portrait that the independent variables in this study were able to provide an explanation of the dependent variable amounted to 95% while 5% is influenced by other variables outside the research such as Import exports, exchange rate, and domestic investment. But Debt Abroad that have promoted high economic growth is apparently not perceived by all parties this is indicated by the ratio of gini already in point 0:41 this means economic growth turned out to be ineffective in reducing poverty and inequality in Indonesia, this makes debt as is an obligation every year will only have an impact on economic growth in the short term and the nominal issued to pay interest repayments make economic growth even if just to pay the interest repayments. Investment in Indonesia today is also increase pertumbukan Indonesian economy, but only within the limits of economic growth alone is not accompanied by a reduction in poverty even every year is precisely the ratio gini Indonesia increasingly large, this may be due to the type of investment in Indonesia is the type of investment capital intensive and requires an educated workforce so as not pushing to reduce povertyKeywords: economic growth, foreign investment, foreign government debt